Dimeric structure of a human apolipoprotein B mRNA editing protein and cloning and chromosomal localization of its gene. - Lau, P P (1994)
Apolipoprotein B (apoB) mRNA editing consists of a posttranscriptional C-->U conversion involving the first base of the codon CAA encoding glutamine-2153 to UAA, a stop codon, in apoB mRNA. Using a cloned rat cDNA as a probe, we cloned the cDNA and genomic sequences of the gene for a human apoB mRNA editing protein. Expression of the cDNA in HepG2 cells results in editing of the intracellular apoB mRNA. By fluorescence in situ hybridization, we localized the gene for the editing protein to chromosome band 12p13.1-p13.2. By Northern blot analysis, it was shown that the human editing protein mRNA is expressed exclusively in the small intestine. The cDNA sequence predicts a translation product of 236-aa residues. By attaching an epitope tag sequence to the C terminus of the editing protein, we examined the polymerization state of the editing protein synthesized in vitro. We found that the editing protein undergoes spontaneous polymerization. The migration of the human apoB mRNA editing protein on an HPLC column and the stoichiometry of polymeric epitope-tagged to untagged protein indicate that the protein exists as a dimer. Dimerization does not require glycosylation of a consensus N-linked glycosylation sequence present in the protein and is not mediated by disulfide bridge formation. The human apoB mRNA editing protein is a cytidine deaminase showing structural homology to some known mammalian and bacteriophage deoxycytidylate deaminases. The latter enzymes exist as homopolymers. The fact that the apoB mRNA editing protein also exists as a homodimer has important implications for the mechanism of apoB mRNA editing in humans.